A flexible neural electrode and a method for preparing the same
By first depositing the electrically polymerized PDA layer at the nerve electrode site and then depositing the electrically polymerized PEDOT layer, the directional polymer chain is formed by electrochemical methods, and the problems of existing neural electrode coatings are solved, achieving higher adhesion, durability and biocompatibility.
Patent Information
- Application Number
- CN202411450090.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-17
AI Technical Summary
In the long-term use of existing neural electrodes, the interface bonding force of the PEDOT coating is weak, which can easily lead to the coating peeling and the electrochemical performance degradation, affecting its stability and reliability.
The method of first depositing the electrically polymerized PDA layer at the electrode site and then depositing the electrically polymerized PEDOT layer is adopted. Two layers of materials are formed by electrochemical methods, and the monomer molecules are guided to be arranged in a directional manner using an external electric field to enhance the interface bonding strength and stability.
It significantly improves the adhesion and durability of the nerve electrode surface, reduces the interface impedance, enhances electrochemical stability, extends service life, and exhibits lower inflammatory response and cytotoxicity in the biological environment.
Smart Images

Figure CN118949266B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedicine and relates to a flexible neural electrode and a preparation method thereof. Background Art
[0002] Neural electrodes are an important biomedical device that is widely used in the fields of neural regulation and brain-computer interface. They stimulate, record and regulate the nervous system by interacting with the electrical signals of neural tissue. In implantable neural electrodes, the material properties of the electrode site surface directly affect its interfacial interaction with neural tissue, which in turn affects the electrochemical properties, biocompatibility and long-term stability of the electrode. Therefore, how to improve the conductivity, stability and biocompatibility of the neural electrode surface has become a key challenge in research.
[0003] In the study of surface modification of neural electrodes, conductive polymers such as PEDOT (poly(3,4-ethylenedioxythiophene)) have been widely used due to their excellent conductivity and biocompatibility. By depositing PEDOT on the surface of neural electrodes, the impedance of the electrode can be significantly reduced, the signal conduction effect can be improved, and the biocompatibility of the electrode can be increased. However, simple PEDOT coatings are prone to coating shedding and performance degradation due to mechanical stress, weak interface bonding, etc. during long-term use, thus affecting its long-term stability and reliability. Therefore, how to further improve the adhesion and durability of the PEDOT coating on the surface of neural electrodes has become the focus of research in this field.
[0004] The literature (Highly Stable Carbon Nanotube Doped Poly(3,4-Ethylenedioxythiophene) for Chronic Neural Stimulation. Biomaterials. 2011Aug;32(24):5551–5557.) uses electrochemical polymerization of PEDOT on the surface of neural electrodes to improve electrode performance. However, the interface bonding strength of PEDOT deposited directly on the surface of the electrode site is weak, and the PEDOT coating is prone to fall off and the electrochemical performance is reduced, especially in long-term use. In addition, although the pulse voltage electropolymerization deposition of PEDOT technology can improve the uniformity and electrochemical performance of the PEDOT layer to a certain extent, its interface bonding strength and stability still need to be further improved. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art and to provide a flexible neural electrode and a preparation method thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A flexible neural electrode comprises a lower packaging layer, a metal conductive layer and an upper packaging layer which are adjacent to each other from bottom to top. The metal conductive layer is composed of a chromium layer located below and a non-chromium metal layer located above. The chromium layer acts as a substrate and an adhesion layer for the non-chromium metal layer. A portion of the metal conductive layer is exposed in the upper packaging layer, and this portion of the metal conductive layer is used as an electrode site. A composite layer is provided on the upper surface of the electrode site, and the composite layer is composed of an electropolymerized PDA (polydopamine) layer located below and an electropolymerized PEDOT layer located above.
[0008] The present invention first deposits an electropolymerized PDA layer on the electrode site and then deposits an electropolymerized PEDOT layer, wherein the electropolymerized PDA layer can provide a better substrate for the electropolymerized PEDOT layer and simultaneously provide chemical functional groups (such as amino groups and phenolic hydroxyl groups) to form stronger chemical bonds with the electropolymerized PEDOT layer, thereby enhancing the stability and biocompatibility of the entire composite layer.
[0009] The PDA layer of the present invention is an electropolymerized PDA layer, the PEDOT layer is an electropolymerized PEDOT layer, and the performance of the "electropolymerized PDA layer + electropolymerized PEDOT layer" is better than that of the "in situ polymerized PDA layer + in situ polymerized PEDOT layer", "in situ polymerized PDA layer + electropolymerized PEDOT layer", and "electropolymerized PDA layer + in situ polymerized PEDOT layer". The specific analysis is as follows:
[0010] The interface bonding strength is higher, which is due to the fact that both layers of materials are formed by electrochemical methods. During the electropolymerization process, the external electric field plays a key role, guiding the monomer molecules to achieve directional arrangement. This directional arrangement mechanism promotes the orderly growth of the polymer chain, significantly reduces the entanglement and disordered structure between molecules, and makes the polymer structure more regular. At the same time, the electrochemical process also activates the substrate surface, and the activated surface is more conducive to forming chemical bonds with the polymer, thereby greatly enhancing the adhesion between the interfaces. Under the combined effect of these factors, not only the interface impedance is reduced, but also the electrochemical stability is significantly improved.
[0011] Fewer structural defects. Compared with in situ polymerization, the electrochemical method can more accurately control the polymerization process and avoid the defects caused by rapid and disordered growth. The low defect density not only improves the mechanical strength of the polymer layer, but also enhances its chemical stability. In contrast, in situ polymerization often relies on spontaneous chemical reactions, and it is difficult to accurately control the thickness and uniformity of the polymer layer, which may lead to uneven bonding between layers, and thus adversely affect the electrochemical properties and overall stability of the composite layer.
[0012] PDA can provide a strong adhesive substrate for neural electrodes, enhance coating stability, improve electrode performance and biocompatibility, and extend service life. The specific analysis is as follows:
[0013] As a polymer with excellent adhesion ability, PDA can form a stable coating on the surface of different types of materials; the PDA layer provides a highly adhesive substrate for the subsequent electrodeposition of PEDOT, allowing PEDOT to firmly adhere to the surface of the electrode site, reducing the possibility of PEDOT coating falling off during use, significantly improving the stability and durability of the PEDOT coating, and thus enhancing the stability of neural electrodes in various environments;
[0014] PDA contains a large number of active functional groups (such as amino groups, hydroxyl groups, etc.), which can chemically bond or physically adsorb with monomers or segments in PEDOT, promoting the firm bonding of PEDOT and the PDA layer; the interface between the electrode site and the PEDOT layer is more tightly bonded, which helps to extend the service life of the neural electrode coating in various environments;
[0015] Although the PDA layer itself has low conductivity, its thin thickness has little effect on the electrochemical performance. The subsequently deposited PEDOT has good conductivity, which can significantly improve the electrochemical performance of the electrode, reduce the electrode impedance and improve the charge transfer capacity of the electrode interface. After being modified with PEDOT, the neural electrode exhibits better conductivity when transmitting electrical signals and conducting electrochemical reactions.
[0016] The PDA layer provides a uniform surface, and the pulse voltage method can adjust the thickness and morphology of the deposition; compared with depositing PEDOT directly on the electrode site, the PDA layer can help form a denser and more uniform coating, improving the overall performance of the neural electrode;
[0017] PDA, as a melanin-like polymer, has good biocompatibility and can reduce the body's rejection of implanted electrodes; PEDOT coating also has good biocompatibility; the combination of the two makes the neural electrodes show lower inflammatory response and cytotoxicity when implanted in the body or in contact with biological tissues, and improves stability and durability in the biological environment;
[0018] The introduction of PDA enhances the adhesion of the coating and provides a more stable underlying foundation for PEDOT, preventing it from degrading or peeling off during multiple electrochemical cycles or in biological environments. Compared with PEDOT deposited alone, the composite coating has better durability and long-lasting performance, extending the service life of the neural electrode.
[0019] As the preferred technical solution:
[0020] In the flexible neural electrode as described above, the thickness of the lower packaging layer and the upper packaging layer are both 6 μm, the thickness of the electropolymerized PDA layer is 10~30 nm, the thickness of the electropolymerized PEDOT layer is 50~1000 nm, the thickness of the chromium layer is 3~10 nm, and the thickness of the non-chromium metal layer is 50~200 nm.
[0021] As described above, the composite layer of the flexible neural electrode has substantially no change in impedance after mechanical ultrasound in a physiological environment simulation fluid for 1 hour, substantially no change in the current curve after 10,000 cycles of pulse testing, and more than 85% of the charge storage capacity of the first cycle after 1,000 cycles of CV (cyclic voltammetry) cycle testing. It can be seen that the composite layer of the flexible neural electrode has excellent stability, because the electropolymerized PDA layer provides a strong attachment basis for the electropolymerized PEDOT layer, and may also play a protective role, reducing the degradation of the electropolymerized PEDOT layer.
[0022] The impedance of the flexible neural electrode at a frequency of 1 kHz is 20-30% of the impedance of the neural electrode at a frequency of 1 kHz. By comparison, it can be seen that after setting the composite layer on the upper surface of the electrode site, the impedance of the neural electrode decreases significantly. This is because a special interface structure is formed between the electropolymerized PDA layer and the electropolymerized PEDOT layer, which enhances the electron transmission efficiency.
[0023] The present invention also provides a method for preparing a flexible neural electrode as described in any of the above items, after the initial neural electrode is treated with oxygen plasma, the initial neural electrode is immersed in a dopamine hydrochloride solution for a first electropolymerization to obtain a neural electrode modified with an electropolymerized PDA layer, and then the neural electrode modified with the electropolymerized PDA layer is immersed in an EDOT solution for a second electropolymerization, and then annealing is performed to obtain a flexible neural electrode.
[0024] The present invention uses an electropolymerization method to modify the electropolymerized PDA layer and the electropolymerized PEDOT layer on the electrode site of the initial neural electrode, which can avoid patterning. In situ polymerization will perform in situ polymerization on the entire electrode immersed in the monomer solution, so electropolymerization patterning is simpler and more effective.
[0025] As the preferred technical solution:
[0026] In the method as described above, the dopamine hydrochloride solution includes sodium dihydrogen phosphate, disodium hydrogen phosphate, water, sodium chloride and dopamine hydrochloride, wherein the concentration of dopamine hydrochloride is 1-2 mg / mL, sodium chloride can provide sufficient ionic strength, and the pH value of the dopamine hydrochloride solution is between 6 and 7.
[0027] The dopamine hydrochloride solution in the prior art is mostly an alkaline solution (Tirs solution), and dopamine hydrochloride will undergo natural oxidation in an alkaline environment. This solution is not suitable for electropolymerization. The dopamine hydrochloride solution of the present invention is a weakly acidic solution. Dopamine can be stably stored for 48 hours in a weakly acidic environment, which is more suitable for electropolymerization.
[0028] The first electropolymerization of the present invention is carried out in an aqueous solution, thereby reducing the problem of residual solvent.
[0029] As described above, the specific process of immersing the initial nerve electrode in the dopamine hydrochloride solution for the first electropolymerization is as follows: the initial nerve electrode is clamped with a platinum clip as the working electrode, a 3×3 cm platinum mesh is used as the counter electrode, and a saturated calomel (SCE) electrode is used as the reference electrode. Cyclic voltammetry deposition is performed at a scanning rate of 10~100mV / s at a potential of -0.6~0.6V vs SCE (this parameter indicates that the potential window of the saturated calomel electrode (SCE) relative to the reference electrode is at -0.6~0.6V). The thickness of the electropolymerized PDA layer can be adjusted by adjusting the number of scans. The thickness of the electropolymerized PDA layer first increases with the increase in the number of scans, and then tends to a maximum value (about 30nm). The thickness of the electropolymerized PDA layer can also be adjusted by adjusting the scan rate. Under the premise of a certain number of scans, the slower the scan rate, the thicker the electropolymerized PDA layer, because a slower scan rate can give more time for monomer oxidation and polymerization reactions.
[0030] There are technical challenges in performing two consecutive electropolymerization processes on the same neural electrode. The electropolymerized PDA layer deposited first will affect the deposition of the electropolymerized PEDOT layer. The present invention controls the scanning rate during cyclic voltammetry deposition to make the electropolymerized PDA layer have low roughness and uniform surface, thereby providing a good surface foundation for the deposition of the electropolymerized PEDOT layer.
[0031] In the method described above, the EDOT solution includes NaPSS (sodium poly(p-styrene sulfonate)), water, and EDOT (3,4-ethylenedioxythiophene), wherein the concentration of EDOT is 0.01-0.1 mol / L.
[0032] The second electropolymerization of the present invention is carried out in an aqueous solution, thereby reducing the problem of residual solvent.
[0033] According to the method described above, the specific process of immersing the nerve electrode modified with the electropolymerized PDA layer into the EDOT solution for the second electropolymerization is as follows: the nerve electrode modified with the electropolymerized PDA layer is clamped by a platinum sheet as the working electrode, a 3×3 cm platinum mesh is used as the counter electrode, and a saturated calomel electrode is used as the reference electrode, and pulse voltage deposition is performed, wherein the pulse voltage includes two stages of voltage, no PEDOT is deposited in the low voltage stage, and PEDOT is deposited in the high voltage stage, the low voltage is 0V, and the time corresponding to the low voltage in one cycle is 0.1~1s, the high voltage is 1.2V, and the time corresponding to the high voltage in one cycle is 0.1~1s, the time corresponding to the high voltage in one cycle / one cycle = duty cycle, 1 / one cycle = frequency, and the thickness of the electropolymerized PEDOT layer can be adjusted by adjusting the number of pulse cycles. When the number of pulse cycles is 10~500, the thickness of the electropolymerized PEDOT layer is about 50~1000nm.
[0034] The electropolymerized PEDOT layer of the present invention is obtained by pulse voltage deposition, while the electropolymerized PEDOT layers in the prior art are all obtained by constant potential deposition or cyclic voltammetric deposition. Cyclic voltammetric deposition, due to repeated changes in potential, will cause the performance of the electropolymerized PEDOT layer to be unstable, and the mechanical properties are not as good as those of the electropolymerized PEDOT layer obtained by pulse voltage deposition or constant potential deposition. Constant potential deposition, due to its faster deposition rate, is prone to depositing an uneven electropolymerized PEDOT layer on the surface of the neural electrode. Pulse voltage deposition is relatively excellent in film uniformity and mechanical properties, and is superior to the other two electro-deposition methods.
[0035] The present invention develops specific pulse parameters (such as frequency, duty cycle, voltage range) to specifically optimize the composite layer composed of an electropolymerized PDA layer located below and an electropolymerized PEDOT layer located above. These parameters are significantly different from the optimal parameters for obtaining an electropolymerized PEDOT layer simply by pulse voltage deposition.
[0036] As described above, the initial neural electrode preparation steps are as follows:
[0037] (a) Cleaning the wafer: Place the wafer in acetone and isopropanol for 5-10 minutes each, blow dry with an air gun, and bake on a 120°C hot plate for 20-30 minutes to remove residual moisture and increase adhesion;
[0038] (b) forming a sacrificial layer on the upper surface of the wafer: using a vacuum thermal evaporation coating apparatus to evaporate (evaporation rate is 0.2 nm / s) an Al sacrificial layer with a thickness of 100 nm to 200 nm on the upper surface of the wafer;
[0039] (c) Forming a lower encapsulation layer on the upper surface of the sacrificial layer and performing photolithographic patterning: SU8-2005 photoresist was spin-coated on the upper surface of the sacrificial layer at a speed of 2000 rpm, baked at 65°C for 1 min, and then baked at 95°C for 2 min. 2 , photolithography under the photolithography condition of illumination time of 2500-4000ms, then baking at 65℃ for 1min, then baking at 95℃ for 3min, after cooling to room temperature, developing with PGMEA (propylene glycol methyl ether acetate) for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0040] (d) Forming a peeling layer on the upper surface of the lower encapsulation layer and performing photolithographic patterning: AZ5214 photoresist was spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, baked at 100 °C for 1 min, and then exposed to light at an intensity of 350-540 mW / cm 2, photolithography under the lithography condition of irradiation time of 400-550ms, developing with positive photoresist developer for about 45s, and then washing the residual developer with deionized water;
[0041] (e) evaporating chromium (evaporation rate of 0.05 nm / s, thickness of 3-10 nm) on the upper surface of the peeling layer, and then evaporating a non-chromium metal (such as gold, evaporation rate of 0.1 nm / s, thickness of 50-200 nm) and then removing the peeling layer to form a metal conductive layer;
[0042] (f) An upper encapsulation layer is formed on the upper surface of the metal conductive layer and patterned by photolithography, so that a portion of the metal conductive layer is exposed on the upper encapsulation layer: SU8-2005 photoresist is spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, first baked at 65°C for 1 min, then baked at 95°C for 2 min, and then heated under a light intensity of 2300-3200 mW / cm 2 , photolithography under the photolithography condition of the illumination time of 2500-4000ms, then baking at 65℃ for 1min, then baking at 95℃ for 3min, after cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0043] (g) Removing the sacrificial layer to obtain the initial neural electrode: The product of step (f) was placed in an Al etching solution (composed of 1 MFeCl3·6H2O and 10 v / v% HCl) and etched for about 1 h.
[0044] Beneficial effects:
[0045] (1) The flexible neural electrode of the present invention has a composite layer composed of an electropolymerized PDA layer located below and an electropolymerized PEDOT layer located above, and the composite layer makes the interface bonding strength of the flexible neural electrode higher and has fewer structural defects; the two layers of materials are formed by an electrochemical method, and the external electric field guides the monomer molecules to align in a directional manner, promotes the orderly growth of the polymer chain, reduces the intermolecular entanglement and disordered structure, makes the polymer structure more regular, and activates the substrate surface, enhances the adhesion between the interfaces, reduces the interface impedance, and significantly improves the electrochemical stability;
[0046] Compared with in situ polymerization, the electrochemical method can more accurately control the polymerization process and avoid the defects caused by rapid and disordered growth; the low defect density not only improves the mechanical strength of the polymer layer, but also enhances its chemical stability, making the composite layer more stable and reliable in long-term use; in addition, the electrochemical method can directly modify the electropolymerized PDA layer and the electropolymerized PEDOT layer at the electrode site of the initial neural electrode, eliminating the need for patterning, which is simpler and more effective than in situ polymerization.
[0047] (2) The PDA layer of the flexible neural electrode of the present invention is a polymer with excellent adhesion ability, which provides a solid base for the electropolymerized PEDOT layer, reduces the possibility of PEDOT coating falling off, and significantly improves the stability and durability of the coating; at the same time, both PDA and PEDOT have good biocompatibility, which can reduce the body's rejection reaction to implanted electrodes, reduce inflammatory reactions and cytotoxicity, and improve stability and durability in the biological environment.
[0048] (3) The dopamine hydrochloride solution used in the present invention is a weakly acidic solution. Dopamine can be stably stored for a long time in a weakly acidic environment and is more suitable for electropolymerization. In addition, both the first electropolymerization and the second electropolymerization are carried out in an aqueous solution, which reduces the problem of solvent residue.
[0049] (4) The present invention controls the scanning rate during cyclic voltammetry deposition to ensure that the roughness of the electropolymerized PDA layer is low and the surface is uniform, thereby providing a good surface foundation for the deposition of the electropolymerized PEDOT layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The present invention is a process for preparing the flexible neural electrode according to Example 1;
[0051] Figure 2 Schematic diagram of a flexible neural electrode device according to Example 1 of the present invention; wherein 1 is a lower packaging layer, 2 is a metal conductive layer, 3 is an electropolymerized PDA layer, 4 is an electropolymerized PEDOT layer, and 5 is an upper packaging layer;
[0052] Figure 3 This is a SEM image of the electropolymerized PEDOT layer of the flexible neural electrode of Example 1 of the present invention;
[0053] Figure 4 This is a SEM image of the electropolymerized PDA layer of the flexible neural electrode of Example 1 of the present invention;
[0054] Figure 5 The impedance comparison between the initial neural electrode and the flexible neural electrode in the embodiment 1 of the present invention in the frequency range of 0.1-100000 Hz;
[0055] Figure 6 A comparison of charge storage capacity between the electrode sites of the flexible neural electrode of Example 1 of the present invention and the electrode sites of the initial neural electrode;
[0056] Figure 7The current curve of the flexible neural electrode of Example 1 of the present invention after 1 to 10000 cycles of pulse testing (using PARSTAT MC 1000 Princeton multi-channel electrochemical workstation, setting the pulse period to 60ms, including 30ms for the high-voltage stage and 30ms for the low-voltage stage, and the pulse voltage low voltage of -0.5V and high voltage of 0.5V);
[0057] Figure 8 The impedance of the flexible neural electrode of Example 1 of the present invention after mechanical ultrasound for 1 hour (using Shanghai Kedao SK5200H high-frequency ultrasonic cleaner, with the ultrasonic power set to 200W) in a physiological environment simulation solution (1xPBS buffer, manufactured by Roan Reagent Company) is compared with the initial impedance;
[0058] Fig. 9 The voltage-current curve of the flexible neural electrode of Example 1 after 1 to 1000 cycles of CV cycle test;
[0059] Fig.10 This is a SEM image of the vapor-phase polymerized PEDOT layer of the flexible neural electrode of Comparative Example 1;
[0060] Fig.11 This is a SEM image of the in-situ polymerized PDA layer of the flexible neural electrode of Comparative Example 1;
[0061] Fig.12 This is a SEM image of the electropolymerized PEDOT layer of the flexible neural electrode of Example 2;
[0062] Fig.13 This is a SEM image of the electropolymerized PEDOT layer of the flexible neural electrode of Example 3. DETAILED DESCRIPTION
[0063] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0064] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0065] The charge storage capacity of the electrode sites after 1000 cycles of CV cycle test and the percentage of charge storage capacity in the first cycle: The 0.5 cm 2Cyclic voltammetry was performed on the electrode sites to obtain the voltage-current curves of the electrode sites after 1 to 1000 cycles of CV cycle testing. The charge storage capacity of the electrode sites after 1 to 1000 cycles of CV cycle testing was calculated by the following formula:
[0066] ;
[0067] In the formula, is the charge storage capacity (unit: mC / cm 2 ), is the upper limit of the potential window, is the lower limit of the potential window, is the current at each potential (in mA), is the area of the electrode site (in cm 2 ), is the scanning rate (V / s);
[0068] Subsequently, the charge storage capacity of the electrode sites after 1000 cycles of CV cycle testing and the percentage of the charge storage capacity in the first cycle were calculated.
[0069] Impedance: The test was performed using a Princeton PARSTAT MC 1000 multi-channel electrochemical workstation in the frequency range of 0.1-100000 Hz to obtain the frequency-impedance curve.
[0070] Example 1
[0071] A method for preparing a flexible neural electrode, the preparation process is as follows Figure 1 As shown, the specific steps are as follows:
[0072] (1) Preparation of materials;
[0073] Wafer;
[0074] acetone;
[0075] Isopropyl alcohol;
[0076] Al;
[0077] SU8-2005 photoresist: manufacturer is Microchem;
[0078] PGMEA: CAS number is 1088-65-6;
[0079] AZ5214 photoresist: The manufacturer is Xi'an Boyan Micro-Nano Information Technology Co., Ltd.;
[0080] Positive photoresist developer: tetramethylammonium hydroxide, manufactured by Jiangyin Jianghua Microelectronics Materials Co., Ltd., model number ZX-238;
[0081] chromium;
[0082] gold;
[0083] Al etching solution: composed of 1M FeCl3·6H2O and 10v / v% HCl;
[0084] Sodium dihydrogen phosphate aqueous solution: concentration is 1 mol / L;
[0085] Disodium hydrogen phosphate aqueous solution: concentration is 1 mol / L;
[0086] NaCl;
[0087] Dopamine hydrochloride: CAS number is 62-31-7;
[0088] NaPSS: CAS number is 25704-18-1;
[0089] Deionized water;
[0090] EDOT: CAS number is 126213-50-1;
[0091] Platinum clip;
[0092] 3×3cm platinum mesh;
[0093] Saturated calomel electrode;
[0094] (2) preparing initial neural electrodes, dopamine hydrochloride solution, and EDOT solution respectively;
[0095] The initial neural electrode preparation process is as follows:
[0096] (a) Cleaning the wafer: Place the wafer in acetone and isopropanol for 5 min each, blow dry with an air gun, and bake on a 120°C hot plate for 20 min;
[0097] (b) forming a sacrificial layer on the upper surface of the wafer: using a vacuum thermal evaporation coating apparatus to evaporate (evaporation rate of 0.2 nm / s) a 100 nm thick Al sacrificial layer on the upper surface of the wafer;
[0098] (c) Forming a lower encapsulation layer on the upper surface of the sacrificial layer and performing photolithographic patterning: SU8-2005 photoresist was spin-coated on the upper surface of the sacrificial layer at a speed of 2000 rpm, baked at 65°C for 1 min, and then baked at 95°C for 2 min. 2 , photolithography under the photolithography condition with the illumination time of 2500ms, then baking at 65℃ for 1min, then baking at 95℃ for 3min, after cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0099] (d) Forming a peeling layer on the upper surface of the lower encapsulation layer and performing photolithographic patterning: AZ5214 photoresist was spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, baked at 100 °C for 1 min, and then patterned under a light intensity of 540 mW / cm 2 , photolithography under the lithography condition with the illumination time of 400ms, developing with positive photoresist developer for about 45s, and then washing the residual developer with deionized water;
[0100] (e) chromium is evaporated on the upper surface of the peeling layer (evaporation rate is 0.05 nm / s) and then gold is evaporated (evaporation rate is 0.1 nm / s) and then the peeling layer is removed to form a metal conductive layer;
[0101] (f) An upper encapsulation layer is formed on the upper surface of the metal conductive layer and patterned by photolithography, so that a portion of the metal conductive layer is exposed on the upper encapsulation layer: SU8-2005 photoresist is spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, first baked at 65°C for 1 min, then baked at 95°C for 2 min, and then heated under a light intensity of 3200 mW / cm 2 , photolithography under the photolithography condition with the illumination time of 2500ms, then baking at 65℃ for 1min, then baking at 95℃ for 3min, after cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0102] (g) Removing the sacrificial layer to obtain an initial neural electrode: placing the product of step (f) in an Al etching solution and etching for about 1 hour to obtain an initial neural electrode;
[0103] The initial neural electrode impedance at a frequency of 1 kHz was 200 Ω;
[0104] The preparation process of the dopamine hydrochloride solution is as follows: 87.7 mL of sodium dihydrogen phosphate aqueous solution is added to 13.3 mL of sodium dihydrogen phosphate aqueous solution, and then 0.8 g of NaCl is added to obtain a PBS buffer solution, and then dopamine hydrochloride is dissolved in the PBS buffer solution to obtain a dopamine hydrochloride solution with a concentration of 1 mg / mL and a pH value of 6;
[0105] The preparation process of EDOT solution is as follows: firstly, NaPSS is dissolved in deionized water to obtain a NaPSS solution with a concentration of 1 mg / mL, and then EDOT is dissolved in the NaPSS solution to obtain an EDOT solution with a concentration of 0.01 mol / L;
[0106] (3) Preparation of flexible neural electrodes;
[0107] (3.1) After the initial neural electrode was treated with oxygen plasma, it was immersed in a dopamine hydrochloride solution, and the initial neural electrode was clamped with a platinum clip as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Cyclic voltammetry was performed at a potential of -0.6~0.6V vs SCE at a scan rate of 10mV / s for 20 cycles to obtain a neural electrode modified with an electropolymerized PDA layer;
[0108] (3.2) The neural electrode modified with the electropolymerized PDA layer was immersed in the EDOT solution, and the neural electrode modified with the electropolymerized PDA layer was clamped with a platinum sheet as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Pulse voltage deposition was performed, and then annealing was performed to obtain a flexible neural electrode; wherein the pulse voltage includes two-stage voltage, the low voltage is 0 V, and the time corresponding to the low voltage in one cycle is 0.1 s, and the high voltage is 1.2 V, and the time corresponding to the high voltage in one cycle is 0.2 s, and the total pulse time is 300 s.
[0109] like Figure 2 As shown, the finally prepared flexible neural electrode consists of a lower packaging layer 1, an upper packaging layer 5, a metal conductive layer 2 and a composite layer; the lower packaging layer 1, the metal conductive layer 2 and the upper packaging layer 5 are adjacent from bottom to top; the metal conductive layer 2 consists of a chromium layer located below and a gold layer located above; the upper packaging layer 5 exposes part of the metal conductive layer 2, and this part of the metal conductive layer 2 is used as an electrode site; the composite layer is located on the upper surface of the electrode site, and consists of an electropolymerized PDA layer 3 located below and an electropolymerized PEDOT layer 4 located above; the thickness of the lower packaging layer 1 and the upper packaging layer 5 are both 6μm, the thickness of the electropolymerized PDA layer 3 is 30nm, the thickness of the electropolymerized PEDOT layer 4 is 125nm, the thickness of the chromium layer is 5nm, and the thickness of the gold layer is 100nm; the charge storage capacity of the electrode site of the flexible neural electrode after 1000 cycles of CV cycle test is 95% of the charge storage capacity of the first cycle (the voltage-current curve of the electrode site of the flexible neural electrode after 1~1000 cycles of CV cycle test is shown in Fig. 9 The impedance of the flexible neural electrode at a frequency of 1kHz is 49Ω.
[0110] SEM images of the electropolymerized PDA layer of the flexible neural electrode Figure 4 As shown, the SEM of the electropolymerized PEDOT layer is Figure 3 As shown, from Figure 3 It can be seen that the surface of the electropolymerized PEDOT layer is uneven, which increases the specific surface area of the electrode site, allowing the flexible neural electrode to store more charge, helping to reduce impedance, and has a dense structure, providing a guarantee for the stability of the flexible neural electrode.
[0111] Impedance comparison of the initial neural electrode and the flexible neural electrode Figure 5 As shown, from Figure 5 It can be seen that compared with the initial neural electrode, the impedance of the flexible neural electrode is reduced at all frequencies. This is because the electropolymerized PEDOT layer of the flexible neural electrode has good charge conduction performance, thereby reducing the overall impedance of the flexible neural electrode; the charge storage capacity of the electrode sites of the flexible neural electrode and the electrode sites of the initial neural electrode is compared. Figure 6 As shown, from Figure 6 It can be seen that compared with the electrode sites of the initial neural electrodes, the charge storage capacity of the electrode sites of the flexible neural electrodes is significantly improved. This is because PEDOT is a pseudocapacitive material with higher charge storage efficiency. Therefore, the PEDOT layer can significantly improve the capacitance and charge storage capacity of the flexible neural electrodes.
[0112] The current curve of the flexible neural electrode after 1 to 10,000 cycles of pulse testing is shown in the figure. Figure 7 As shown, from Figure 7 It can be seen that after 10,000 cycles of pulse testing, the current curve of the flexible neural electrode has basically not changed. The peak values of the current curves of the first cycle and the 10,000th cycle are both 34.72 mA / cm 2 , indicating that the flexible neural electrode has good electrochemical stability; the impedance of the flexible neural electrode after mechanical ultrasound in physiological environment simulation fluid for 1 hour is compared with the initial impedance. Figure 8 As shown, from Figure 8 It can be seen that after 1 hour of mechanical ultrasound in the physiological environment simulated fluid, the impedance of the flexible nerve electrode remained basically unchanged. Its impedance at a frequency of 1 kHz increased from the original 49Ω to 60Ω, and there was no increase in impedance in the low-frequency region, indicating that the flexible nerve electrode has good mechanical stability.
[0113] Comparative Example 1
[0114] A method for preparing a flexible neural electrode is basically the same as that of Example 1, except that: in step (2), no dopamine hydrochloride solution and EDOT solution are prepared; the specific process of step (3) is as follows:
[0115] (3.1) First, Tirs (tris(hydroxymethyl)aminomethane, CAS No. 1185-53-1) was added to water to obtain a Tirs buffer solution with a concentration of 0.1 mol / L, and then dopamine hydrochloride was dissolved in the Tirs buffer solution to obtain a dopamine hydrochloride solution with a concentration of 1 mg / mL. Then, the initial neural electrode was immersed in the dopamine hydrochloride solution for 2 h and then rinsed with deionized water to obtain a neural electrode modified with an in situ polymerized PDA layer;
[0116] (3.2) First, dissolve 2 g of ferric p-toluenesulfonate and 0.2 g of pyridine in 5 mL of butanol to obtain an oxidant solution. Then, apply 200 μL of the oxidant solution on the neural electrode modified with the in situ polymerized PDA layer and bake it on a 70°C hot plate for 2 min. Then, apply 200 μL of EDOT on a clean glass slide. Place the neural electrode modified with the in situ polymerized PDA layer and the glass slide on a vacuum hot plate, respectively. Heat to 70°C, evacuate to -76 cmHg, and perform gas phase polymerization for 30 min to obtain a flexible neural electrode.
[0117] The final composite layer of the flexible neural electrode is composed of an in-situ polymerized PDA layer (SEM Fig.11 ) and gas phase polymerized PEDOT layer (SEM as Fig.10 The thickness of the in-situ polymerized PDA layer is 35 nm, and the thickness of the vapor-phase polymerized PEDOT layer is 130 nm; the charge storage capacity of the electrode site of the flexible neural electrode after 1000 cycles of CV cycle testing is 50% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1 kHz is 160 Ω.
[0118] Compared with Example 1 and Comparative Example 1, the charge storage capacity of the electrode sites of the flexible neural electrode decreased significantly after 1000 cycles of CV cycle testing, and the impedance of the flexible neural electrode at a frequency of 1 kHz increased significantly. This is because the "in situ polymerization PDA layer + vapor phase polymerization PEDOT layer" relies on spontaneous chemical reactions, and it is difficult to accurately control the thickness and uniformity of the polymer layer, resulting in uneven bonding between layers, which affects the electrochemical properties and stability of the flexible neural electrode.
[0119] Comparative Example 2
[0120] A method for preparing a flexible neural electrode is basically the same as that of Example 1, except that: in step (2), no dopamine hydrochloride solution is prepared; the specific process of step (3) is as follows:
[0121] (3.1) First, Tirs (CAS No. 1185-53-1) was added to water to obtain a Tirs buffer solution with a concentration of 0.1 mol / L, and then dopamine hydrochloride was dissolved in the Tirs buffer solution to obtain a dopamine hydrochloride solution with a concentration of 1 mg / mL. Then, the initial neural electrode was immersed in the dopamine hydrochloride solution for 2 h and then rinsed with deionized water to obtain a neural electrode modified with an in situ polymerized PDA layer;
[0122] (3.2) The neural electrode modified with the in situ polymerized PDA layer was immersed in the EDOT solution, and the neural electrode modified with the in situ polymerized PDA layer was clamped with a platinum sheet as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode, and pulse voltage deposition was performed, followed by annealing to obtain a flexible neural electrode; wherein the pulse voltage includes two-stage voltages, the low voltage is 0 V, and the time corresponding to the low voltage in one cycle is 0.1 s, and the high voltage is 1.2 V, and the time corresponding to the high voltage in one cycle is 0.2 s, and the total pulse time is 300 s.
[0123] The composite layer of the flexible neural electrode finally prepared consists of an in situ polymerized PDA layer and an electropolymerized PEDOT layer; the thickness of the in situ polymerized PDA layer is 35nm; the charge storage capacity of the electrode site of the flexible neural electrode after 1000 cycles of CV cycle test is 80% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz is 90Ω.
[0124] Compared with Example 1 and Comparative Example 2, the charge storage capacity of the electrode sites of the flexible neural electrode decreased significantly after 1000 cycles of CV cycle testing, and the impedance of the flexible neural electrode at a frequency of 1 kHz increased significantly. This is because it is difficult to accurately control the thickness and uniformity of the in-situ polymerized PDA layer, and the interlayer bonding is uneven, which affects the electrochemical properties and overall stability of the composite layer.
[0125] Comparative Example 3
[0126] A method for preparing a flexible neural electrode is basically the same as that of Example 1, except that: in step (2), no EDOT solution is prepared; the specific process of step (3) is as follows:
[0127] (3.1) After the initial neural electrode was treated with oxygen plasma, it was immersed in a dopamine hydrochloride solution, and the initial neural electrode was clamped with a platinum clip as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Cyclic voltammetry was performed at a potential of -0.6~0.6V vs SCE at a scan rate of 10mV / s for 20 cycles to obtain a neural electrode modified with an electropolymerized PDA layer;
[0128] (3.2) First, dissolve 2 g of ferric p-toluenesulfonate and 0.2 g of pyridine in 5 mL of butanol to obtain an oxidant solution. Then, apply 200 μL of the oxidant solution on the neural electrode modified with the electropolymerized PDA layer and bake it on a 70°C hot plate for 2 min. Then, apply 200 μL of EDOT on a clean glass slide. Place the neural electrode modified with the electropolymerized PDA layer and the glass slide on a vacuum hot plate, respectively. Heat to 70°C, evacuate to -76 cmHg, and perform gas phase polymerization for 30 min to obtain a flexible neural electrode.
[0129] After 1000 cycles of CV cycle testing, the charge storage capacity of the electrode site of the flexible neural electrode finally produced was 70% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz was 80Ω.
[0130] Compared with Example 1 and Comparative Example 3, the charge storage capacity of the electrode sites of the flexible neural electrode decreased significantly after 1000 cycles of CV cycle testing, and the impedance of the flexible neural electrode at a frequency of 1 kHz increased significantly. This is because the uniformity of the vapor-phase polymerized PEDOT layer is poor, resulting in unsatisfactory conductivity and weak interlayer bonding, which affects the electrochemical properties and overall stability of the composite layer.
[0131] Comparative Example 4
[0132] A method for preparing a flexible neural electrode is basically the same as that of Example 1, except that step (3) is as follows:
[0133] (3.1) After the initial neural electrode is treated with oxygen plasma, it is immersed in the EDOT solution, and the initial neural electrode is clamped with a platinum sheet clip as the working electrode, a 3×3 cm platinum mesh is used as the counter electrode, and a saturated calomel electrode is used as the reference electrode, and pulse voltage deposition is performed to obtain a neural electrode with a modified electropolymerized PEDOT layer; wherein the pulse voltage includes two-stage voltages, the low voltage is 0 V, and the time corresponding to the low voltage in one cycle is 0.1 s, and the high voltage is 1.2 V, and the time corresponding to the high voltage in one cycle is 0.2 s, and the total pulse time is 300 s;
[0134] (3.2) The neural electrode modified with the electropolymerized PEDOT layer was immersed in a dopamine hydrochloride solution, and the initial neural electrode was clamped with a platinum sheet as the working electrode, a 3×3 cm platinum mesh was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. Cyclic voltammetry was performed at a potential of -0.6~0.6 V vs SCE at a scanning rate of 10 mV / s for 20 cycles, and then annealing was performed to obtain a flexible neural electrode.
[0135] The composite layer of the flexible neural electrode finally prepared is composed of an electropolymerized PDA layer and an electropolymerized PEDOT layer, and the electropolymerized PDA layer is located above the electropolymerized PEDOT layer; the charge storage capacity of the electrode site of the flexible neural electrode after 1000 cycles of CV cycle test is 45% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz is 165Ω.
[0136] Compared with Example 1, the charge storage capacity of the electrode site of the flexible neural electrode decreased significantly after 1000 cycles of CV cycle test, and the impedance of the flexible neural electrode at a frequency of 1 kHz increased significantly. This is because the PEDOT layer is directly deposited at the electrode site by electropolymerization in Comparative Example 4, and there is no PDA layer as an adhesion layer, so the mechanical stability and adhesion are poor; and the surface morphology of the first deposited PEDOT layer is disordered and rough. This uneven surface will affect the subsequent electropolymerization of the PDA layer, making it impossible for the PDA layer to form a uniform coating on the surface of the PEDOT layer, thereby increasing the electrode interface impedance, and the low conductivity PDA layer as an outer layer will block the conductive channel of the PEDOT layer, further affecting the interface impedance.
[0137] Example 2
[0138] A method for preparing a flexible neural electrode is basically the same as that in Example 1, except that: Step (3.2) is: immersing the neural electrode modified with an electropolymerized PDA layer into an EDOT solution, clamping the neural electrode modified with an electropolymerized PDA layer with a platinum clip as a working electrode, a 3×3 cm platinum mesh as a counter electrode, and a saturated calomel electrode as a reference electrode, and continuously applying a constant potential voltage of 1.1 V vs SCE for 40 s to obtain a flexible neural electrode.
[0139] After 1000 cycles of CV cycle testing, the charge storage capacity of the electrode site of the flexible neural electrode finally produced was 88% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz was 50Ω.
[0140] Compared with Example 1, the charge storage capacity of the electrode site of the flexible neural electrode decreased after 1000 cycles of CV cycle test, and the impedance of the flexible neural electrode at a frequency of 1kHz increased. This is because Example 2 adopts constant potential deposition to obtain the electropolymerized PEDOT layer (the SEM of the electropolymerized PEDOT layer deposited by constant potential of the flexible neural electrode of Example 2 is as follows: Fig.12 As shown in the figure, constant potential deposition can easily deposit an uneven electropolymerized PEDOT layer on the surface of the neural electrode due to its fast deposition rate, resulting in a decrease in the performance of the composite layer.
[0141] Example 3
[0142] A method for preparing a flexible neural electrode is basically the same as that in Example 1, except that: Step (3.2) is: immersing the neural electrode modified with an electropolymerized PDA layer into an EDOT solution, clamping the neural electrode modified with an electropolymerized PDA layer with a platinum clip as a working electrode, a 3×3 cm platinum mesh as a counter electrode, and a saturated calomel electrode as a reference electrode, and performing cyclic potential deposition for 50 cycles at a scanning rate of 0.1 V / s at a potential of 0-1.5 V vs SCE to obtain a flexible neural electrode.
[0143] After 1000 cycles of CV cycle testing, the charge storage capacity of the electrode site of the flexible neural electrode finally produced was 87% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz was 60Ω.
[0144] Compared with Example 1, the charge storage capacity of the electrode sites of the flexible neural electrode decreased after 1000 cycles of CV cycle testing, and the impedance of the flexible neural electrode at a frequency of 1 kHz increased. This is because Example 3 uses cyclic potential deposition to obtain the electropolymerized PEDOT layer. Due to the repeated changes in potential of cyclic voltammetric deposition, the performance of the electropolymerized PEDOT layer is not stable enough and the mechanical properties are poor, which affects the electrochemical properties and overall stability of the composite layer.
[0145] SEM images of the electropolymerized PEDOT layer of the flexible neural electrode of Example 3 Fig.13 As shown, compared Figure 3 , Fig.12 , Fig.13 It can be seen that compared with Example 1, the film formation uniformity of the electropolymerized PEDOT layer of the flexible neural electrodes of Examples 2 and 3 is poor, and the surface is irregular island agglomerates. It can be seen that pulse voltage deposition is relatively excellent in film formation uniformity and mechanical properties, and is superior to constant potential deposition and cyclic voltammetry deposition.
[0146] Example 4
[0147] A method for preparing a flexible neural electrode is basically the same as that in Example 1, except that: Step (3.2) is: immersing the neural electrode modified with an electropolymerized PDA layer into an EDOT solution, clamping the neural electrode modified with an electropolymerized PDA layer with a platinum sheet clamp as a working electrode, a 3×3 cm platinum mesh as a counter electrode, and a saturated calomel electrode as a reference electrode, performing pulse voltage deposition, and then performing annealing treatment to obtain the flexible neural electrode; wherein the pulse voltage includes two-stage voltages, the low voltage is 0V, the time corresponding to the low voltage in one cycle is 0.1s, the high voltage is 1.1V, the time corresponding to the high voltage in one cycle is 0.2s, and the total pulse time is 300s.
[0148] After 1000 cycles of CV cycle testing, the charge storage capacity of the electrode site of the flexible neural electrode finally produced was 85% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz was 56Ω.
[0149] In Example 4 compared with Example 1, the charge storage capacity of the electrode sites of the flexible neural electrode decreased after 1000 cycles of CV cycle test, and the impedance of the flexible neural electrode at a frequency of 1 kHz increased. This is because the high voltage value of the pulse voltage used in Example 4 is the optimal parameter for obtaining the electropolymerized PEDOT layer simply by pulse voltage deposition, and this value is low. The electropolymerized PDA layer will affect the charge transfer process, and a higher overpotential is required to better deposit the electropolymerized PEDOT layer.
[0150] Example 5
[0151] A method for preparing a flexible neural electrode, the specific steps are as follows:
[0152] (1) Preparation of materials;
[0153] Wafer;
[0154] acetone;
[0155] Isopropyl alcohol;
[0156] Al;
[0157] SU8-2005 photoresist: manufacturer is Microchem;
[0158] PGMEA: CAS number is 1088-65-6;
[0159] AZ5214 photoresist: The manufacturer is Xi'an Boyan Micro-Nano Information Technology Co., Ltd.;
[0160] Positive photoresist developer: tetramethylammonium hydroxide, manufactured by Jiangyin Jianghua Microelectronics Materials Co., Ltd., model number ZX-238;
[0161] chromium;
[0162] gold;
[0163] Al etching solution: composed of 1M FeCl3·6H2O and 10v / v% HCl;
[0164] Sodium dihydrogen phosphate aqueous solution: concentration is 1 mol / L;
[0165] Disodium hydrogen phosphate aqueous solution: concentration is 1 mol / L;
[0166] NaCl;
[0167] Dopamine hydrochloride: CAS number is 62-31-7;
[0168] NaPSS: CAS number is 25704-18-1;
[0169] Deionized water;
[0170] EDOT: CAS number is 126213-50-1;
[0171] Platinum clip;
[0172] 3×3cm platinum mesh;
[0173] Saturated calomel electrode;
[0174] (2) preparing initial neural electrodes, dopamine hydrochloride solution, and EDOT solution respectively;
[0175] The initial neural electrode preparation process is as follows:
[0176] (a) Cleaning the wafer: Place the wafer in acetone and isopropanol for 6 minutes each, blow dry with an air gun, and bake on a 120°C hot plate for 25 minutes;
[0177] (b) forming a sacrificial layer on the upper surface of the wafer: using a vacuum thermal evaporation coating apparatus to evaporate (evaporation rate of 0.2 nm / s) a 140 nm thick Al sacrificial layer on the upper surface of the wafer;
[0178] (c) Forming a lower encapsulation layer on the upper surface of the sacrificial layer and performing photolithographic patterning: SU8-2005 photoresist was spin-coated on the upper surface of the sacrificial layer at a speed of 2000 rpm, first baked at 65°C for 1 min, then baked at 95°C for 2 min, and then heated under a light intensity of 3000 mW / cm 2 , photolithography under the photolithography condition with the illumination time of 3000ms, then baking at 65℃ for 1min, then baking at 95℃ for 3min, after cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0179] (d) Forming a peeling layer on the upper surface of the lower encapsulation layer and performing photolithographic patterning: AZ5214 photoresist was spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, baked at 100 °C for 1 min, and then exposed to light at an intensity of 480 mW / cm 2 , photolithography under the lithography condition with an illumination time of 480ms, developing with a positive photoresist developer for about 45s, and then washing the residual developer with deionized water;
[0180] (e) chromium is evaporated on the upper surface of the peeling layer (evaporation rate is 0.05 nm / s) and then gold is evaporated (evaporation rate is 0.1 nm / s) and then the peeling layer is removed to form a metal conductive layer;
[0181] (f) An upper encapsulation layer is formed on the upper surface of the metal conductive layer and patterned by photolithography, so that a portion of the metal conductive layer is exposed on the upper encapsulation layer: SU8-2005 photoresist is spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, first baked at 65°C for 1 min, then baked at 95°C for 2 min, and then heated under a light intensity of 3000 mW / cm 2 , photolithography under the photolithography condition with the illumination time of 3000ms, then baking at 65℃ for 1min, then baking at 95℃ for 3min, after cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0182] (g) Removing the sacrificial layer to obtain an initial neural electrode: placing the product of step (f) in an Al etching solution and etching for about 1 hour to obtain an initial neural electrode;
[0183] The initial neural electrode impedance at 1 kHz was 190 Ω;
[0184] The preparation process of the dopamine hydrochloride solution is as follows: 81.5 mL of sodium dihydrogen phosphate aqueous solution is added to 18.5 mL of sodium dihydrogen phosphate aqueous solution, and then 0.8 g of NaCl is added to obtain a PBS buffer solution, and then dopamine hydrochloride is dissolved in the PBS buffer solution to obtain a dopamine hydrochloride solution with a concentration of 1.5 mg / mL and a pH value of 6.2;
[0185] The preparation process of EDOT solution is as follows: firstly, NaPSS is dissolved in deionized water to obtain a NaPSS solution with a concentration of 5 mg / mL, and then EDOT is dissolved in the NaPSS solution to obtain an EDOT solution with a concentration of 0.02 mol / L;
[0186] (3) Preparation of flexible neural electrodes;
[0187] (3.1) After the initial neural electrode was treated with oxygen plasma, it was immersed in a dopamine hydrochloride solution, and the initial neural electrode was clamped with a platinum sheet as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Cyclic voltammetry was performed at a potential of -0.6~0.6V vs SCE at a scan rate of 20mV / s for 5 cycles to obtain a neural electrode modified with an electropolymerized PDA layer;
[0188] (3.2) The neural electrode modified with the electropolymerized PDA layer was immersed in the EDOT solution, and the neural electrode modified with the electropolymerized PDA layer was clamped with a platinum sheet as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Pulse voltage deposition was performed, and then annealing was performed to obtain a flexible neural electrode; wherein the pulse voltage includes two-stage voltage, the low voltage is 0 V, and the time corresponding to the low voltage in one cycle is 0.2 s, and the high voltage is 1.2 V, and the time corresponding to the high voltage in one cycle is 0.1 s, and the total pulse time is 1000 s.
[0189] The final flexible neural electrode consists of a lower packaging layer, an upper packaging layer, a metal conductive layer and a composite layer; the lower packaging layer, the metal conductive layer and the upper packaging layer are adjacent to each other from bottom to top; the metal conductive layer consists of a chromium layer located below and a gold layer located above; the upper packaging layer exposes part of the metal conductive layer, which is used as an electrode site; the composite layer is located on the upper surface of the electrode site, and consists of an electropolymerized PDA layer located below and an electropolymerized PEDOT layer located above; the thickness of the lower packaging layer and the upper packaging layer are both 6μm, the thickness of the electropolymerized PDA layer is 10nm, the thickness of the electropolymerized PEDOT layer is 200nm, the thickness of the chromium layer is 3nm, and the thickness of the gold layer is 60nm; the charge storage capacity of the electrode site of the flexible neural electrode after 1000 cycles of CV cycle testing is 92% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz is 45Ω.
[0190] Example 6
[0191] A method for preparing a flexible neural electrode, the specific steps are as follows:
[0192] (1) Preparation of materials;
[0193] Wafer;
[0194] acetone;
[0195] Isopropyl alcohol;
[0196] Al;
[0197] SU8-2005 photoresist: manufacturer is Microchem;
[0198] PGMEA: CAS number is 1088-65-6;
[0199] AZ5214 photoresist: The manufacturer is Xi'an Boyan Micro-Nano Information Technology Co., Ltd.;
[0200] Positive photoresist developer: tetramethylammonium hydroxide, manufactured by Jiangyin Jianghua Microelectronics Materials Co., Ltd., model number ZX-238;
[0201] chromium;
[0202] gold;
[0203] Al etching solution: composed of 1M FeCl3·6H2O and 10v / v% HCl;
[0204] Sodium dihydrogen phosphate aqueous solution: concentration is 1 mol / L;
[0205] Disodium hydrogen phosphate aqueous solution: concentration is 1 mol / L;
[0206] NaCl;
[0207] Dopamine hydrochloride: CAS number is 62-31-7;
[0208] NaPSS: CAS number is 25704-18-1;
[0209] Deionized water;
[0210] EDOT: CAS number is 126213-50-1;
[0211] Platinum clip;
[0212] 3×3cm platinum mesh;
[0213] Saturated calomel electrode;
[0214] (2) preparing initial neural electrodes, dopamine hydrochloride solution, and EDOT solution respectively;
[0215] The initial neural electrode preparation process is as follows:
[0216] (a) Cleaning the wafer: Place the wafer in acetone and isopropanol for 8 minutes each, blow dry with an air gun, and bake on a 120°C hot plate for 25 minutes;
[0217] (b) forming a sacrificial layer on the upper surface of the wafer: using a vacuum thermal evaporation coating apparatus to evaporate (evaporation rate of 0.2 nm / s) an Al sacrificial layer with a thickness of 180 nm on the upper surface of the wafer;
[0218] (c) Forming a lower encapsulation layer on the upper surface of the sacrificial layer and performing photolithographic patterning: SU8-2005 photoresist was spin-coated on the upper surface of the sacrificial layer at a speed of 2000 rpm, baked at 65°C for 1 min, and then baked at 95°C for 2 min. 2 , photolithography under the photolithography condition with an illumination time of 3500ms, then baking at 65°C for 1min, then baking at 95°C for 3min, cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0219] (d) Forming a peeling layer on the upper surface of the lower encapsulation layer and performing photolithographic patterning: AZ5214 photoresist was spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, baked at 100 °C for 1 min, and then exposed to light at an intensity of 420 mW / cm 2 , photolithography under the lithography condition with the illumination time of 520ms, developing with positive photoresist developer for about 45s, and then washing the residual developer with deionized water;
[0220] (e) chromium is evaporated on the upper surface of the peeling layer (evaporation rate is 0.05 nm / s) and then gold is evaporated (evaporation rate is 0.1 nm / s) and then the peeling layer is removed to form a metal conductive layer;
[0221] (f) An upper encapsulation layer is formed on the upper surface of the metal conductive layer and patterned by photolithography, so that a portion of the metal conductive layer is exposed on the upper encapsulation layer: SU8-2005 photoresist is spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, first baked at 65°C for 1 min, then baked at 95°C for 2 min, and then heated under a light intensity of 2500 mW / cm 2 , photolithography under the photolithography condition with an illumination time of 3500ms, then baking at 65°C for 1min, then baking at 95°C for 3min, cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0222] (g) Removing the sacrificial layer to obtain an initial neural electrode: placing the product of step (f) in an Al etching solution and etching for about 1 hour to obtain an initial neural electrode;
[0223] The initial neural electrode impedance at 1 kHz was 160 Ω;
[0224] The preparation process of the dopamine hydrochloride solution is as follows: 68.5 mL of sodium dihydrogen phosphate aqueous solution is added to 31.5 mL of sodium dihydrogen phosphate aqueous solution, and then 0.8 g of NaCl is added to obtain a PBS buffer solution, and then dopamine hydrochloride is dissolved in the PBS buffer solution to obtain a dopamine hydrochloride solution with a concentration of 1.8 mg / mL and a pH value of 6.5;
[0225] The preparation process of EDOT solution is as follows: firstly, NaPSS is dissolved in deionized water to obtain a NaPSS solution with a concentration of 8 mg / mL, and then EDOT is dissolved in the NaPSS solution to obtain an EDOT solution with a concentration of 0.05 mol / L;
[0226] (3) Preparation of flexible neural electrodes;
[0227] (3.1) After the initial neural electrode was treated with oxygen plasma, it was immersed in a dopamine hydrochloride solution, and the initial neural electrode was clamped with a platinum clip as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Cyclic voltammetry was performed at a potential of -0.6~0.6V vs SCE at a scan rate of 50mV / s for 10 cycles to obtain a neural electrode modified with an electropolymerized PDA layer;
[0228] (3.2) The neural electrode modified with the electropolymerized PDA layer was immersed in the EDOT solution, and the neural electrode modified with the electropolymerized PDA layer was clamped with a platinum sheet as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Pulse voltage deposition was performed, and then annealing was performed to obtain a flexible neural electrode; wherein the pulse voltage includes two-stage voltage, the low voltage is 0 V, and the time corresponding to the low voltage in one cycle is 0.5 s, and the high voltage is 1.2 V, and the time corresponding to the high voltage in one cycle is 0.5 s, and the total pulse time is 500 s.
[0229] The final flexible neural electrode consists of a lower packaging layer, an upper packaging layer, a metal conductive layer and a composite layer; the lower packaging layer, the metal conductive layer and the upper packaging layer are adjacent to each other from bottom to top; the metal conductive layer consists of a chromium layer located below and a gold layer located above; the upper packaging layer exposes part of the metal conductive layer, and this part of the metal conductive layer is used as an electrode site; the composite layer is located on the upper surface of the electrode site, and consists of an electropolymerized PDA layer located below and an electropolymerized PEDOT layer located above; the thickness of the lower packaging layer and the upper packaging layer are both 6μm, the thickness of the electropolymerized PDA layer is 20nm, the thickness of the electropolymerized PEDOT layer is 1000nm, the thickness of the chromium layer is 8nm, and the thickness of the gold layer is 200nm; the charge storage capacity of the electrode site of the flexible neural electrode after 1000 cycles of CV cycle test is 90% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz is 40Ω.
[0230] Example 7
[0231] A method for preparing a flexible neural electrode, the specific steps are as follows:
[0232] (1) Preparation of materials;
[0233] Wafer;
[0234] acetone;
[0235] Isopropyl alcohol;
[0236] Al;
[0237] SU8-2005 photoresist: manufacturer is Microchem;
[0238] PGMEA: CAS number is 1088-65-6;
[0239] AZ5214 photoresist: The manufacturer is Xi'an Boyan Micro-Nano Information Technology Co., Ltd.;
[0240] Positive photoresist developer: tetramethylammonium hydroxide, manufactured by Jiangyin Jianghua Microelectronics Materials Co., Ltd., model number ZX-238;
[0241] chromium;
[0242] gold;
[0243] Al etching solution: composed of 1M FeCl3·6H2O and 10v / v% HCl;
[0244] Sodium dihydrogen phosphate aqueous solution: concentration is 1 mol / L;
[0245] Disodium hydrogen phosphate aqueous solution: concentration is 1 mol / L;
[0246] NaCl;
[0247] Dopamine hydrochloride: CAS number is 62-31-7;
[0248] NaPSS: CAS number is 25704-18-1;
[0249] Deionized water;
[0250] EDOT: CAS number is 126213-50-1;
[0251] Platinum clip;
[0252] 3×3cm platinum mesh;
[0253] Saturated calomel electrode;
[0254] (2) preparing initial neural electrodes, dopamine hydrochloride solution, and EDOT solution respectively;
[0255] The initial neural electrode preparation process is as follows:
[0256] (a) Cleaning the wafer: Place the wafer in acetone and isopropanol for 10 min each, blow dry with an air gun, and bake on a 120°C hot plate for 30 min;
[0257] (b) forming a sacrificial layer on the upper surface of the wafer: using a vacuum thermal evaporation coating apparatus to evaporate (evaporation rate of 0.2 nm / s) a 200 nm thick Al sacrificial layer on the upper surface of the wafer;
[0258] (c) Forming a lower encapsulation layer on the upper surface of the sacrificial layer and performing photolithographic patterning: SU8-2005 photoresist was spin-coated on the upper surface of the sacrificial layer at a speed of 2000 rpm, baked at 65°C for 1 min, and then baked at 95°C for 2 min. 2 , photolithography under the photolithography condition with the illumination time of 4000ms, then baking at 65℃ for 1min, then baking at 95℃ for 3min, after cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0259] (d) Forming a peeling layer on the upper surface of the lower encapsulation layer and performing photolithographic patterning: AZ5214 photoresist was spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, baked at 100 °C for 1 min, and then exposed to light at an intensity of 350 mW / cm 2 , photolithography under the lithography condition with an illumination time of 550ms, developing with a positive photoresist developer for about 45s, and then washing the residual developer with deionized water;
[0260] (e) chromium is evaporated on the upper surface of the peeling layer (evaporation rate is 0.05 nm / s) and then gold is evaporated (evaporation rate is 0.1 nm / s) and then the peeling layer is removed to form a metal conductive layer;
[0261] (f) An upper encapsulation layer is formed on the upper surface of the metal conductive layer and patterned by photolithography, so that a portion of the metal conductive layer is exposed on the upper encapsulation layer: SU8-2005 photoresist is spin-coated on the upper surface of the lower encapsulation layer at a speed of 2000 rpm, first baked at 65°C for 1 min, then baked at 95°C for 2 min, and then heated under a light intensity of 2300 mW / cm 2 , photolithography under the photolithography condition with the illumination time of 4000ms, then baking at 65℃ for 1min, then baking at 95℃ for 3min, after cooling to room temperature, developing with PGMEA for about 70s, then spraying PGMEA for about 10s, and then washing the residual developer with isopropyl alcohol;
[0262] (g) Removing the sacrificial layer to obtain an initial neural electrode: placing the product of step (f) in an Al etching solution and etching for about 1 hour to obtain an initial neural electrode;
[0263] The initial neural electrode impedance at 1 kHz was 250 Ω;
[0264] The preparation process of the dopamine hydrochloride solution is as follows: 39 mL of sodium dihydrogen phosphate aqueous solution is added to 61 mL of sodium dihydrogen phosphate aqueous solution, and then 0.8 g of NaCl is added to obtain a PBS buffer solution, and then dopamine hydrochloride is dissolved in the PBS buffer solution to obtain a dopamine hydrochloride solution with a concentration of 2 mg / mL and a pH value of 7;
[0265] The preparation process of EDOT solution is as follows: firstly, NaPSS is dissolved in deionized water to obtain a NaPSS solution with a concentration of 10 mg / mL, and then EDOT is dissolved in the NaPSS solution to obtain an EDOT solution with a concentration of 0.1 mol / L;
[0266] (3) Preparation of flexible neural electrodes;
[0267] (3.1) After the initial neural electrode was treated with oxygen plasma, it was immersed in a dopamine hydrochloride solution, and the initial neural electrode was clamped with a platinum sheet as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Cyclic voltammetry was performed at a potential of -0.6~0.6V vs SCE at a scan rate of 100mV / s for 50 cycles to obtain a neural electrode modified with an electropolymerized PDA layer;
[0268] (3.2) The neural electrode modified with the electropolymerized PDA layer was immersed in the EDOT solution, and the neural electrode modified with the electropolymerized PDA layer was clamped with a platinum sheet as the working electrode, a 3×3 cm platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Pulse voltage deposition was performed, and then annealing was performed to obtain a flexible neural electrode; wherein the pulse voltage includes two-stage voltages, the low voltage is 0 V, and the time corresponding to the low voltage in one cycle is 1 s, and the high voltage is 1.2 V, and the time corresponding to the high voltage in one cycle is 1 s, and the total pulse time is 10 s.
[0269] The final flexible neural electrode consists of a lower packaging layer, an upper packaging layer, a metal conductive layer and a composite layer; the lower packaging layer, the metal conductive layer and the upper packaging layer are adjacent to each other from bottom to top; the metal conductive layer consists of a chromium layer located below and a gold layer located above; the upper packaging layer exposes part of the metal conductive layer, which is used as an electrode site; the composite layer is located on the upper surface of the electrode site, and consists of an electropolymerized PDA layer located below and an electropolymerized PEDOT layer located above; the thickness of the lower packaging layer and the upper packaging layer are both 6μm, the thickness of the electropolymerized PDA layer is 30nm, the thickness of the electropolymerized PEDOT layer is 50nm, the thickness of the chromium layer is 10nm, and the thickness of the gold layer is 50nm; the charge storage capacity of the electrode site of the flexible neural electrode after 1000 cycles of CV cycle testing is 96% of the charge storage capacity of the first cycle; the impedance of the flexible neural electrode at a frequency of 1kHz is 60Ω.
Claims
1. A method for preparing a flexible neural electrode, characterized in that: After the initial neural electrode is treated with oxygen plasma, the initial neural electrode is immersed in a dopamine hydrochloride solution for a first electropolymerization to obtain a neural electrode modified with an electropolymerized PDA layer, and then the neural electrode modified with an electropolymerized PDA layer is immersed in an EDOT solution for a second electropolymerization, and then annealed to obtain a flexible neural electrode; The specific process of immersing the modified electropolymerized PDA layer neural electrode into the EDOT solution for the second electropolymerization is as follows: the neural electrode modified electropolymerized PDA layer is clamped by a platinum sheet as the working electrode, the platinum mesh is the counter electrode, and the saturated calomel electrode is the reference electrode, and pulse voltage deposition is performed, wherein the pulse voltage includes two-stage voltages, the low voltage is 0V, and the time corresponding to the low voltage in one cycle is 0.1~1s, and the high voltage is 1.2V, and the time corresponding to the high voltage in one cycle is 0.1~1s; The flexible neural electrode includes a lower packaging layer, a metal conductive layer and an upper packaging layer which are adjacent to each other from bottom to top. The upper packaging layer exposes a portion of the metal conductive layer, which is used as an electrode site. A composite layer is provided on the upper surface of the electrode site, and the composite layer is composed of an electropolymerized PDA layer located below and an electropolymerized PEDOT layer located above.
2. The method for preparing a flexible neural electrode according to claim 1, characterized in that: The dopamine hydrochloride solution comprises sodium dihydrogen phosphate, disodium hydrogen phosphate, water, sodium chloride and dopamine hydrochloride, wherein the concentration of the dopamine hydrochloride is 1-2 mg / mL, and the pH value of the dopamine hydrochloride solution is between 6 and 7.
3. The method for preparing a flexible neural electrode according to claim 1, characterized in that: The specific process of immersing the initial nerve electrode in the dopamine hydrochloride solution for the first electropolymerization is: the initial nerve electrode is clamped with a platinum clip as the working electrode, the platinum mesh is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode, and cyclic voltammetry deposition is performed at a potential of -0.6~0.6V vs SCE at a scanning rate of 10~100mV / s.
4. The method for preparing a flexible neural electrode according to claim 1, characterized in that: The EDOT solution includes NaPSS, water, and EDOT, wherein the concentration of EDOT is 0.01-0.1 mol / L.
5. The method for preparing a flexible neural electrode according to claim 1, characterized in that: The initial neural electrode preparation steps are as follows: a. Clean the wafer; b. forming a sacrificial layer on the upper surface of the wafer; c. forming a lower encapsulation layer on the upper surface of the sacrificial layer and performing photolithography patterning; d. forming a peeling layer on the upper surface of the lower encapsulation layer and performing photolithography patterning; e. After evaporating metal on the upper surface of the peeling layer, remove the peeling layer to form a metal conductive layer; f. forming an upper packaging layer on the upper surface of the metal conductive layer and performing photolithography patterning so that a portion of the metal conductive layer is exposed from the upper packaging layer; g. Remove the sacrificial layer to obtain the initial neural electrode.
6. The method for preparing a flexible neural electrode according to claim 1, characterized in that: The thickness of the lower encapsulation layer and the upper encapsulation layer are both 6 μm, the thickness of the electropolymerized PDA layer is 10-30 nm, and the thickness of the electropolymerized PEDOT layer is 50-1000 nm.
Citation Information
Patent Citations
Flexible electrode for spinal cord and method for manufacturing same
WO2023240695A1